Impactos socio culturales de las empresas florícolas en la comunidad jurídica Cananvalle durante los últimos 30 años - Quimbiamba Cacuango, Pedro (2015)
The study of the socio cultural impacts of the flower industries in the “Cananvalle” commune entails the last 30 years of an Andean commune in the North Sierra of Ecuador. For this purpose the proposed theoretical and methodological frame engulfs the key topics of identity, interculturality and the complex processes of communalization and dis communalization of the social tissue in this territory. In this perspective, the presentation of the results of this study begins with the characterization of the “Cananvalle” commune, from the focus of its location, its demographics and its organizational processes. The research also presents the results of the characterization of the flower industries, especially regarding its productive and labor strategies, as well as its relation with the surrounding communities from local to province and national span. The characterization of the main actors in this territory it’s the foundation for the further analysis of the impacts of the flower production in the social and community organization aspects. It’s also matter of this analysis the dynamics inside the change in the familiar agriculture as a consequence of the new forms of insertion in local markets and thus, the abandon of the family crop that traditionally supplied food for the local families.